Government Political Communication In Packaging the Policy Message for the Existence of Non-State Civil Apparatus Workers for Strengthening Public Service - Hkikmat, Mahi Mamat (Badan Pembinaan Hukum Nasional, 2022)
AbstractOne of the problems of the government's staffing policy is political communication which is less relevant to the democratic political system between the political superstructure and political infrastructure. What is the reality of the Government's political communication in the non-state civil apparatus manpower management policy and what kind of political communication model can be developed in the non-state civil apparatus manpower management policy. By using an interpretive subjective approach, qualitative research methods, and descriptive research types, it was found that there were problems of political communication carried out by the Government as a political superstructure in issuing political policy messages in the form of legislation related to the management of Non-State Civil Apparatus. A sound political communication model is an option that must be developed by building positive interactions between the Government and employees, so as to get an explicit response regarding the pure aspirations of honorary workers and outsourcing workers.